2012
DOI: 10.1177/1066896912449042
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Incidentally Detected Thyroid Tissue in Lymph Nodes of Neck Dissections in Patients With Head and Neck Carcinoma

Abstract: The study's results emphasize the need for the clinician to do an accurate reevaluation and follow-up of patients with incidental occult metastasis for detection of primary thyroid tumor. A thorough sampling and screening of lymph nodes in neck dissection specimens by the pathologist is also essential. Incidentally discovered thyroid tissue in cervical lymph nodes need not always be benign inclusions. Aggressive therapy, however, may not be needed in all cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…This finding not only inflicts additional suffering and financial burden on the patients, but also implies the possible need for further treatments and surgeries. Kr et al (10) suggested that incidental lymph node metastasis from thyroid cancer found during head and neck should prompt the search for the primary lesion.…”
Section: Original Articlementioning
confidence: 99%
“…This finding not only inflicts additional suffering and financial burden on the patients, but also implies the possible need for further treatments and surgeries. Kr et al (10) suggested that incidental lymph node metastasis from thyroid cancer found during head and neck should prompt the search for the primary lesion.…”
Section: Original Articlementioning
confidence: 99%
“…The occurrence of two synchronous, primary cancers of different origin in the head and neck region is even more rare. A literature search on Pubmed (see Appendix 1) yielding over 1300 hits, revealed incidences of synchronous primary thyroid gland tumor discovered in the resection specimen of a patient with head and neck cancer, between 0.3 and 1.9% [19] , [20] , [21] , [22] . Resta et al [21] presented eight cases in which incidental metastases of well-differentiated thyroid gland carcinoma were found in lymph nodes of patients with squamous cell carcinoma without clinical signs of thyroid disease.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of two synchronous, primary cancers of different origin in the head and neck region is rare. Thyroid carcinoma is found incidentally in the resection specimen after surgery for head and neck cancer in 0.3–1.9% of the patients [19] , [20] , [21] , [22] .…”
Section: Introductionmentioning
confidence: 99%
“…However, the possibility that some of these deposits are nodal primaries deriving from benign thyroid inclusions is now considered. Table 1 catalogues cases reported since 1999 [1220]. Although reservations may be expressed regarding efficacy of serial sectioning/thoroughness of histological examination of the entire thyroid, the fact that seven out of 27 subsequent thyroidectomies did not show evidence of PTC (26%, Table 1) makes out a case for the aforementioned possibility.…”
Section: Recent Investigationsmentioning
confidence: 99%
“…Although the latter regarded the FTC deposits as micrometastases, the thyroid was histologically free from tumour and the possibility that they corresponded with nodal thyroid inclusions cannot be excluded. A case of an incidental medullary carcinoma has also been reported [20]. …”
Section: Recent Investigationsmentioning
confidence: 99%